Design of broadband high efficiency absorption antenna based on metamaterial nano-ring array - Li, Na; Tian, Yanwei; Bao, Jianqiang; Wang, Yan; Zhao, Chi (Frontiers in Materials, 2022)
Compared with the traditional solar cells, the nano-optical antenna breaks through the band-gap limitation of semiconductor materials, and provides a new scheme for solar energy collection. In order to solve the problems of complex structure, low efficiency and narrow bandwidth of nano-optical antenna, a novel nano-ring-cylinder based on metamaterials is proposed in this paper. The antenna has an average absorption efficiency of 96.93% in the wide-band absorption range of visible and near-infrared light. First of all, the basic design theory of the antenna was given based on the surface plasma theory. Then, the antenna structure design scheme was determined, the overall structure consists of two layers of metal and an insulating layer formed by Al2O3. Finally, on the basis of the established antenna model, the absorption characteristics were analyzed by simulation. The analysis result shows that the super-absorption ability of the antenna is independent of the polarization of the incident light, and the average absorption ability can be maintained at about 91% when the incident angle is ±60°. The absorption capability of the antenna is mainly due to the synergistic effect of Fabry-Perot resonance and localized surface plasmon resonance enhancement. The conclusion can provide a theoretical guidance for the structural design of nano-optical antenna.